Biocomposites reinforced by fibers or tubes as scaffolds for tissue engineering or regenerative medicine. Issue 5 (7th June 2013) - Li, Xiaoming; Yang, Yu; Fan, Yubo; Feng, Qingling; Cui, Fu‐zhai; Watari, Fumio
Abstract As a dynamic and hierarchically organized composite, native extracellular matrix (ECM) not only supplies mechanical support, which the embedded cells need, but also regulates various cellular activities through interaction with them. On the basis of the ECM‐mimetic principle, good biocompatibility and appropriate mechanical properties are the two basic requirements that the ideal scaffolds for the tissue engineering or regenerative medicine need. Some fibers and tubes have been shown effective to reinforce scaffolds for tissue engineering or regenerative medicine. In this review, three parts, namely properties affected by the addition of fibers or tubes, scaffolds reinforced by fibers or tubes for soft tissue repair, and scaffolds reinforced by fibers or tubes for hard tissue repair are stated, which shows that tissue repair or regeneration efficacy was enhanced significantly by fiber or tube reinforcement. In addition, it indicates that these reinforcing agents can improve the biocompatibility and biodegradation of the scaffolds in most cases. However, there are still some concerns, such as the homogeneousness in structure or composition throughout the reinforced scaffolds, the adhesive strength between the matrix and the fibers or tubes, cytotoxicity of nanoscaled reinforcing agents, etc., which were also discussed in the conclusion and perspectives part. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1580–1594, 2014.